The effect of oxygen and hydroxide ion on electrochemical leaching behavior of tin - Kim, S.; Lee, J.; Jeong, J.; Yoo, Kyoungkeun (Japan Institute of Metals and Materials, 2012)
The dissolution of tin from waste Pb-free solder was electrochemically investigated in NaOH solution. Two oxidation peaks were observed in a cyclic voltammetry test in 1 kmolm-3 NaOH solution at less than 45°C, and the peaks indicate the oxidation of tin to Sn2+ and Sn 2+ to Sn4+, whereas only one peak was observed at 75°C resulting from the direct oxidation of tin to Sn4+. The increase in NaOH concentration and the introduction of oxygen enhanced the dissolution of tin in NaOH solution with less than 0.5 kmolm-3 whereas that of tin decreased with increasing NaOH concentration further to 1.5 kmolm-3 and the decrease in the dissolution of tin was accelerated by introducing oxygen. An optimum waste solder alkaline electrolysis process was found to be at more than 75°C and around 0.5 kmolm-3 NaOH based on the cyclic voltammetry and constant current experiment.